REKONSTRUKSI MANAJEMEN DAKWAH HUMANIS PERSPEKTIF ABDURRAHMAN WAHID (GUS DUR) DALAM KONTEKS KEBERAGAMAN INDONESIA DI ERA DIGITAL - Oktavia Wardani, Cicin; Kusumawati, Erna; Igrit Alita, Risa; Mamlu’ul Hikmah, Nia; Solikhudin, Anang (STKIP Subang, 2026)
This study examines the reconstruction of a humanistic da’wah management model from the perspective of Abdurrahman Wahid within the context of Indonesia’s diversity in the digital era. The background of this research is based on the gap between the ideal concept of humanistic da’wah, which emphasizes tolerance, pluralism, and humanity, and the contemporary practices of da’wah that often tend to be exclusive and less adaptive to social changes, particularly in digital spaces. This study aims to reconstruct a systematic and applicable model of humanistic da’wah management and to analyze its relevance in the digital era. The research employs a qualitative approach with a library research method, utilizing primary and secondary data sources related to Gus Dur’s thoughts, humanistic da’wah, and digital transformation. The data are analyzed using a descriptive-analytical technique combined with conceptual and contextual approaches. The findings indicate that humanistic values can be integrated into the management functions of da’wah, including planning, organizing, actuating, and evaluating. Furthermore, the reconstructed model is highly relevant in addressing contemporary challenges, such as intolerance and misinformation in digital media. This study contributes theoretically to the development of da’wah management studies and practically offers a reference for implementing inclusive, moderate, and adaptive da’wah in modern society.